Peterborough and the Soke - British Archaeological Association.
1 online resource.
Keywords: The British Archaeological Association Conference held at Peterborough in 2015 provided a welcome opportunity for a new analysis of the cathedral's architecture, sculpture and artistic production, and a reassessment of the relationship between the former abbey, the city and its institutions, and the Soke over which it held sway. This ambitious volume casts new light on the Roman occupation of the Nene valley, and the rich Anglo-Saxon sculptural and manuscript context that preceded the construction of the present cathedral, as well as exploring the vital Romanesque tradition of the Soke and the essential contribution of the Barnack quarries. But inevitably the most exciting new disclosures concern the church: its high-quality building campaigns during the 12th to 16th centuries, its abbots' tombs and the reconstruction of the lost 14th-century High Altar screen from descriptions and loose fragments. Peterborough has attracted the attention of antiquarian scholars since its sacking by Cromwell's men during the Civil War, and as its secrets are gradually revealed it continues to stimulate the historical imagination.